Coxiella burnetii Shedding During the Peripartum Period and Subsequent Fertility in Dairy Cattle. Issue 3 (29th October 2012) - Garcia‐Ispierto, I; López‐Helguera, I; Tutusaus, J; Serrano, B; Monleón, E; Badiola, JJ; López‐Gatius, F
Contents The objective of this study was to assess the effects of Coxiella burnetii shedding or seropositivity on post‐partum recovery and subsequent fertility in high‐producing dairy cows. Given the difficulty in diagnosing C. burnetii infection at the farm level, an exhaustive series of tests in 43 pregnant animals that delivered at least one live calf were conducted, including blood serology and PCR of milk or colostrum, cotyledons (only at parturition), faeces, vaginal fluid against C. burnetii on gestation Day 171–177, at parturition and on Days 1–7, 8–14, 15–21, 22–28, 29–35 and 90–97 post‐partum. During scheduled herd visits, ultrasonography (US) of the genital tract and examination of vaginal fluid were performed on Days 15–21 (V1), 22–28 (V2), 29–35 (V3) and 51–57 (V4) post‐partum by the same veterinarian. Logistic regression analysis revealed that the likelihood of suffering endometritis (the presence of echogenic intrauterine fluid (IUF), cervical diameter of ≥4 cm or endometrial thickness ≥0.75 cm) was lower in C. burnetii‐seropositive animals (OR = 0.10), compared with C. burnetii‐seronegative animals. According to Kaplan–Meier survival analysis, C. burnetii‐seronegative and non‐shedding cows showed a delayed return to luteal activity and conception was delayed in non‐shedding animals, compared with the remaining animals. Overall, the results of our study provide useful insight into the effects of C. burnetii infection on post‐partum recovery and subsequent fertility. In particular, animals not infected with Coxiella seem to be susceptible to infection and not protected against the bacterium in dairy herds. The elevated costs of determining an infection at the farm level, make monitoring of cows virtually impossible from a clinical point of view.